Massive change - Mau, Bruce; Leonard, Jennifer; Institute without Boundaries (London ; New York : Phaidon Press Limited, 2005)
Includes transcripts of interviews with: Philip Ball, Janine Benyus, Stewart Brand, Stephen Browne, Carol Burns, James Der Derian, Bill Drayton, Gwynne Dyer, Freeman Dyson, Ian Foster, Felice Frankel, Robert Freling, Ashok Gadgil, Catherine Gray, Hazel Henderson, Dean Kamen, Arthur Kroker, Robert S. Langer, Jaime Lerner, Lawrence Lessig, David Malin, Michael McDonough, William McDonough, Seymour Melman, Nancy Padian, Matt Ridley, Jeffrey Sachs, Richard Smalley, Hernando de Soto, Bruce Sterling and Eugene Thacker.
Urban economies (URB) -- Movement economies (MOV) -- Energy economies (ENE) -- Information economies (INF) -- Image economies (IMA) -- Market economies (MAR) -- Material economies (MAT) -- Military economies (MIL) -- Manufacturing economies (MAN) -- Living economies (LIV) -- Wealth and politics (WP).
"Massive Change is an ambitious project that humbly attempts to chart the bewildering complexity of our increasingly interconnected (and designed) world ... We hope to make evident the design decisions that go on and are made manifest across disciplines"--P. [11].
Includes bibliographical references (pages [234-236]) and index.
ARC
Department of Architecture
Keywords: Industrial design; Multidisciplinary design optimization; Social change -- Forecasting; Social ecology -- Forecasting; Architecture